2004
DOI: 10.1021/jp049591w
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Kinetic Modeling of Silicon Nanoparticle Formation Chemistry via Automated Mechanism Generation

Abstract: Thermal decomposition of silane can be used to produce silicon nanoparticles, which have attracted great interest in recent years because of their novel optical and electronic properties. However, these silicon nanoparticles are also an important source of particulate contamination leading to yield loss in conventional semiconductor processing. In both cases, a fundamental knowledge of the reaction kinetics of particle formation is needed to understand and control the nucleation of silicon particles. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 34 publications
(76 reference statements)
4
68
1
Order By: Relevance
“…Our observation is in line with results by Wong et al [27], who have modelled silicon nanoparticle formation via automated mechanism generation. At a simulated reactor temperature 750°C and an initial concentration of 10% SiH 4 in H 2 , these authors report cyclopentasilane to be the most abundant pentasilane species.…”
Section: Application To Silane Reactor Monitoringsupporting
confidence: 93%
See 2 more Smart Citations
“…Our observation is in line with results by Wong et al [27], who have modelled silicon nanoparticle formation via automated mechanism generation. At a simulated reactor temperature 750°C and an initial concentration of 10% SiH 4 in H 2 , these authors report cyclopentasilane to be the most abundant pentasilane species.…”
Section: Application To Silane Reactor Monitoringsupporting
confidence: 93%
“…[13][14][15][16][17][18][19][20] and by modelling [see e.g. 13,16,[20][21][22][23][24][25][26][27], have been conducted to broaden the understanding of the monosilane pyrolysis. It is commonly accepted that the pyrolysis occurs through a series of chemical reactions, including SiASi bond formation and hydrogen elimination, producing silanes with increasing number of Si atoms [13,20,22,23,28,29].…”
Section: Pyrolysis Of Sih 4 In Solar Silicon Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies of silane decomposition kinetics have been reported (Becerra and Walsh 1992;Ho et al 1994;Moffat et al 1992a, b;Purnell and Walsh 1984;Wong et al 2004). As in Dang and Swihart (2008), this work used an extensive chemical kinetic mechanism for silicon hydride cluster formation during silane pyrolysis (Swihart and Girshick 1999).…”
Section: Cfd Simulationmentioning
confidence: 98%
“…-coke formation (Moustafa and Froment, 2003;QuintanaSolórzano et al, 2005), -biomass conversion (Rangarajan et al, 2010), -oxidative coupling of methane (Simon et al, 2007), -silicon hydride clustering (Wong et al, 2004), -hydrocarboxylation , -carbonylation (Bruk et al, 1998), -organic synthesis (Fontain and Reitsam, 1991), -biological processes (Valdes-Perez, 1992b;Klein et al, 2002;Faeder et al, 2003Faeder et al, , 2005Li et al, 2004;Hatzimanikatis et al, 2004Hatzimanikatis et al, , 2005Blinov et al, 2005a, b;Mayeno et al, 2005;Henry et al, 2007Henry et al, , 2010Hill et al, 2008;Finley et al, 2009), -and many more.…”
Section: Simulation Of Large Complex Reaction Network 421 Network mentioning
confidence: 99%